The dialectic of the relationship between the organization’s strategy and the organizational structure - a field study in a sample of Jordanian organizations - جمال عبد الرسول غانم الدباغ; نعمة عباس خضير الخفاجي (Iraqi Journal for Administrative Sciences, 2024)
Compatible in its organizational structure pattern; It requires a change in the dynamics of the variables of the organizational structure. The study with the analytical approach specializes in verifying the dialectic of the relationship between the organization’s strategy, represented by strategies of growth, stability, and contraction, and the variables of the organizational structure in its automatic and organic types. The verification took two forms: the first is a theoretical orientation to the idea and the second is a practical, realistic orientation. The questionnaire was distributed as a tool to measure the organization’s strategy and organizational structure to a random sample of (124) managers working in a group of organizations with diverse goals and tasks. The theoretical approach led to the conclusion that there is a dialectical interrelation between the organization’s strategy and its organizational structure. The results of the field study demonstrated that there is partial support for the relationships of growth strategies with most organizational structure variables. Hence, a change in the organization’s strategies requires an appropriate strategic response. The results showed a relative difference in the organization’s strategy. And partly in the organizational structure; Regarding the opinions of the managers of the organizations investigated.